Representing Ethnicity in Cinema during Turkey’s Kurdish Initiative: A Critical Analysis of My Marlon and Brando (Karabey, 2008), The Storm (Öz, 2008) and Future Lasts Forever (Alper, 2011) - Göztepe, Mustafa Orhan; KOÇER, ZEYNEP (Film and Screen Media at University College Cork, Ireland, 2017)
In 2009, the Turkish government started the “Kurdish Initiative”, a comprehensive policymaking process, in an attempt to improve the democratic standards and civil rights of the Kurdish population. Even though the initiative ended in 2015, it made it possible for a significant number of independent films to emerge which deal with the Kurdish issue. Historically, mainstream cinema’s symbolic representation of Kurdish identity served to neutralise its Kurdish characters by portraying them as Turkish speaking and one-dimensional. Breaking this tradition, these independent films offer multi-layered, Kurdish speaking characters with progressive narratives. This article investigates three films produced on the eve of and during the “Kurdish Initiative”: My Marlon and Brando (Gitmek: Benim Marlon ve Brandom, Hüseyin Karabey, 2008), The Storm (Bahoz, Kazım Öz, 2008) and Future Lasts Forever (Gelecek Uzun Sürer, Özcan Alper, 2011). In addition to interrupting the traditional acceptance of stereotypes by the mainstream cinema, each film discusses the symbolic representations of Kurdish identity through different aspects: transnationality, the role of discriminative processes, and memory and trauma.